PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POWTOON TERHADAP KEMAMPUAN BERFIKIR TINGKAT TINGGI PADA PEMBELAJARAN IPA SISWA SEKOLAH DASAR - Tiara Jihan Jamilah; Muh Erwinto Imran; Amri Amal (LPPM Universitas Muhammadiyah Bulukumba, 2024)
This research aims to determine the effect of the Problem Based Learning (PBL) model assisted by Powtoon media on high-level thinking abilities in science learning for V grade students at SDN Tabang No. 24 Selayar Islands. The type of research used is an experiment in the form of Pre-Experimental Design which uses a one group pretest-posttest design. The sample in this study were all class V students of SDN Tabang No. 24 Selayar Islands as many as 17 students. Data collection was carried out using observation sheets, tests and documentation. The research instrument used was a high-level thinking ability test instrument in the form of description, observation and documentation questions. The data analysis technique used is descriptive statistical analysis and inferential analysis, namely the normality test and hypothesis test (paired sample t test). The results of the pretest data research (before using the PBL model assisted by Powtoon media) were that the average value obtained was 52.47. Meanwhile, the average posttest score (after using the PBL model assisted by Powtoon media) was 82.59, which is considered high. After analyzing inferential statistics using the paired sample t test, a sig (2 tailed) value of 0.001 was obtained and the test rules determined were 0.05, then the significance level value was obtained ˂ sign value 0.05 or 0.001 ˂ 0.05. Based on the results obtained, it can be concluded that is rejected and is accepted, this shows that the use of the PBL model assisted by Powtoon media has an effect on high-level thinking abilities in science learning for V grade students at SDN Tabang No. 24 Selayar Islands.